The contribution of PrEP programmes to triple elimination efforts: a cross-sectional study of status and opportunities - Martin, Catherine E.; Ramatsoma, Hlologelo; Koloane, Nthabiseng; Monametsi, Maletsatsi; Arries, Sean; Pleaner, Melanie; Mullick, Saiqa (Frontiers in Reproductive Health, 2025)
BackgroundThe Triple Elimination initiative is a global effort aimed at eliminating vertical transmission of HIV, hepatitis B and syphilis. This paper describes HIV, syphilis and hepatitis B testing and diagnosis in young women and men accessing sexual and reproductive health services and identifies opportunities to integrate prevention interventions.MethodsThe study was conducted in eight primary healthcare and four mobile clinics in South Africa, integrating HIV PrEP within prevention services. Programme data were collected and analysed from women and men ≥15 years accessing services for the first time between June 2023 and March 2024.ResultsOf 10,007 clients, 89.4% were female and 65.5% 18─24 years. Overall, 70.9% were provided HIV PrEP. Among females, 16.8% were provided contraceptives for the first time. HIV was identified in 1.2% of males and 2.2% of females tested and with results available, syphilis in 5.6% and 5.0%, and hepatitis B in 1.7% and 0.9% respectively. An HIV diagnosis was less likely among older age groups and those enrolled in school and more likely among those with part-time relative to full-time employment. Syphilis was less likely among older age groups and those reporting consistent condom use. Hepatitis B was more likely among those who had used oral PrEP before.ConclusionsOpportunities for integrated prevention interventions, aligned to triple elimination, include condom programming, contraception, point-of-care testing, PrEP and vaccination. Integrated care delivered through HIV prevention programmes provides an opportunity to treat and prevent HIV, syphilis and hepatitis B, and offer contraception to prevent unintended pregnancies.